2019
DOI: 10.1088/1361-6560/ab12aa
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for fast image simulation of flat panel detectors

Abstract: We have developed a novel method for fast image simulation of flat panel detectors, based on the photon energy deposition efficiency and the optical spread function (OSF). The proposed method, FastEPID, determines the photon detection using photon energy deposition and replaces particle transport within the detector with precalculated OSFs. The FastEPID results are validated against experimental measurement and conventional Monte Carlo simulation in terms of modulation transfer function (MTF), signal-to-noise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…This work has demonstrated that with cine EPID image frame‐by‐frame analysis, multiple beam delivery error modes can be detected with high sensitivity and low FPR by comparing observed with expected MLC formed apertures. The method is applicable to both pretreatment and during‐treatment real‐time QA, and avoids the need to compute through‐patient transmission fluences in real time at 100 ms per frame 29 for the delivery specific dMU intervals. MLC motion during frame delivery and MLC in‐tolerance position variations can be accounted for in real time via masking of the permissible MLC leaf positions from the frame image.…”
Section: Discussionmentioning
confidence: 99%
“…This work has demonstrated that with cine EPID image frame‐by‐frame analysis, multiple beam delivery error modes can be detected with high sensitivity and low FPR by comparing observed with expected MLC formed apertures. The method is applicable to both pretreatment and during‐treatment real‐time QA, and avoids the need to compute through‐patient transmission fluences in real time at 100 ms per frame 29 for the delivery specific dMU intervals. MLC motion during frame delivery and MLC in‐tolerance position variations can be accounted for in real time via masking of the permissible MLC leaf positions from the frame image.…”
Section: Discussionmentioning
confidence: 99%
“…These two factors result in simulation times often as long as 3,000 core‐hours for a 10 7 primary x‐ray simulation of one EPID projection 9 . Further, to produce a clinically equivalent image of 1 MU with a 10 × 10 cm 2 field size a simulation with more than 10 11 photons is required 10–12 . This problem is compounded in CBCT simulation, where it is necessary to simulate many projections of the object for CBCT image reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Shi et al. introduced the fastEPID framework which pre‐calculates energy deposition efficiency (η) and optical spread function (OSF) to remove particle transport in the detector entirely without loss of image quality 10 . Where η is defined as the ratio of the total energy deposition in the scintillator and the total x‐ray photon energy incident on the detector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Processing the images of slits, [1][2][3][4][5] bar patterns [6][7][8][9] and edge objects [10][11][12][13][14][15][16][17][18] are commonly used methods for measuring the MTF. The edge method is the one recommended by the International Electrotechnical Commission.…”
Section: Introductionmentioning
confidence: 99%